THE IMPACT OF JOB STRESS ON JOB PERFORMANCE AT THE CLASS IIA PAMEKASAN CORRECTIONAL INSTITUTION - Makki, Afif; Wibowo, Padmono (Universitas Nusa Cendana, 2025)
At Pamekasan Class IIA Prison, job performance must be maintained in a comfortable and prosperous manner because employees are an asset to the organization. However, job stress can result in decreased employee performance because of excessive demands and tasks. This study aims to analyze the effect of job stress on job performance at Pamekasan Class IIA Prison. The research method used is quantitative, and SPSS is a statistical tool for assistance. The population was 130 people, and a sample of 97 people was taken with probability sampling and random sampling techniques. The result of the significance test shows the effect of job stress on job performance at Class IIA Pamekasan Correctional Facility is 27.9%, and the other 72.1% is influenced by other variables. Keywords: Job Performance; Class IIA Pamekasan Prison; Job Stress